STRATEGI PENGEMBANGAN EKOWISATA HUTAN MANGROVE DI DESA PERANCAK KABUPATEN JEMBRANA BALI - Rani Setyaningrum; I Nyoman Sudiarta; I Putu Sudana (Jurnal IPTA)
The mangrove forest ecotourism area in Perancak Village, Jembrana Regency is one of the tourist attractions that has interesting potential to be developed. However, there are emerging problems such as a decrease in the number of visits, lack of promotion, and lack of infrastructure improvement, so there is a need for a strategy and program for the development of mangrove forest ecotourism that pays attention to the sustainability aspect of tourism. The purpose of this study is to analyze and formulate a strategy for the development of mangrove forest ecotourism program as a sustainable tourism attraction in Perancak Village. The data analysis techniques used are qualitative descriptive and SWOT analysis with data collection techniques through observation, interviews, literature studies, and documentation. The results of the study show that the ecotourism of the Perancak mangrove forest has tourism potential that can be developed. The development strategies and programs that are considered effective to support the development of Perancak mangrove ecotourism are the diversification of educational tourism products by creating mangrove conservation day and sustainable fishing programs, strengthening the quality of tourism products through infrastructure improvement programs and the recruitment of local tour guides, the use of digital media by creating social media accounts accompanied by videos of ecotourism potential, the preparation of ecotourism branding materials Highlight visual elements and interesting stories of ecotourism, strengthen the quality of local communities through socialization and empowerment of the local economy, partnerships with private institutions and other tourism businesses, add tourist attraction facilities, improve the quality of the ecotourism environment and increase involvement and cooperation with external parties.